Making Insulin Accessible: Does Inhaled Insulin Fill an Unmet Need?. Issue 8 (August 2016) - McGill, Janet; Ahn, David; Edelman, Steven; Kilpatrick, C.; Santos Cavaiola, Tricia
Abstract Glycemic control is fundamental to the management of diabetes. However, studies suggest that a significant proportion of people with diabetes, particularly those using insulin, are not achieving glycemic targets. The reasons for this are likely to be multifactorial. The real and perceived risk of hypoglycemia and the need for multiple daily injections are widely recognized as key barriers to effective insulin therapy. Therefore, there is a clear unmet need for a treatment option which can help mitigate these barriers. Alternative methods of insulin administration have been under investigation for several years, and pulmonary delivery has shown the most promise to date. Inhaled Technosphere® Insulin (TI; Afrezza® ; MannKind Corporation) was approved in 2014 for use as prandial insulin in people with diabetes. TI shows a more rapid onset of action and a significantly faster decline in activity than current subcutaneous rapid-acting insulin analogs (RAAs), and TI is more synchronized to the physiologic timing of the postprandial glucose excursion. This results in lower postprandial hypoglycemia with similar glycemic control compared with RAAs, and less weight gain. Together with the ease of use of the TI inhaler and the reduction in the number of daily injections, these findings imply that TI may be useful in helping to overcome patient resistance to insulin, improve adherence and mitigate clinical inertia in health-care providers, with potential beneficial effects on glycemic control. Funding: Writing and editorial support in the preparation of this publication was funded by Sanofi US, Inc., Bridgewater, New Jersey, USA. Funding for the article processing charges for this publication was provided by MannKind Corporation.